Morphological, phytochemical, and essential oil changes induced by different nitrogen supply forms and salinity stress in Echinacea purpurea L. (August 2022) - Ahmadi, Fatemeh; Samadi, Abbas; Sepehr, Ebrahim; Rahimi, Amir; Shabala, Sergey
Abstract: Salinity is one of the most important environmental factors that affect the plants growth and phytochemical compounds. So, this study was aimed to investigate the effect of salinity stress (15 mM, 30 mM, and 60 mM NaCl) and different NO3 − /NH4 + ratios (90:10; 80:20, and 70:30) on Echinacea purpurea properties in greenhouse conditions. A wide range of morphological properties and phytochemical compounds were determined based on the standard methods. Essential oil analyses was performed by using GC-Mass spectrometer. According to the results, plant height, total biomass, and fresh root weight decreased by 49.6, 43.2, 40.5% after the application of 60 mM NaCl, compared with control plants. However, an increase in total leaf phenolic content, flavonoid content, PAL enzyme activity, super oxide, and nitric oxide anti-radical scavenging activities by 44, 37.2, 57.9, 46, and 27.2% were found in plants grown under 30 mM NaCl salt stress conditions, respectively compared with control plants. The major terpene hydrocarbons found in the E. purpurea extract were germacrene D (60.3%), myrcene (19.8%), α-pinene (13.1%), β-caryophyllene (12.3%), and 1-Pentadecene (5.1%), respectively. It can be concluded that, 30 mM NaCl and 90:10 NO3 − /NH4 + ratio are effective for improving phytochemical properties of E. purpurea . Highlights: The highest phytochemicals were found in 30 mM NaCl salinity level. Germacrene D was found as the most abundant terpene. 60 mM NaCl salinity level decreased the plant yield. 90:10 NO3 − /NH4 + increased the essential oil content.